The impact of lockdown announcements during the COVID-19 crisis: An event study from the Portuguese stock market - Galarza, Manuel Segundo Abreu de Lima (2022)
The COVID-19 pandemic impacted global financial markets in an unprecedented manner. It is well-documented the negative effect in stock markets and increased volatility caused by the preventive measures adopted to combat the disease. This study aims to analyse how lockdowns and other restrictive measures affected the Portuguese index PSI-20 and its constituents. Specially, it investigates the effect over the three first waves of COVID-19 in Portugal, using the STOXX600 European index as benchmark, between March 2020 and April 2021. To test the hypothesis of whether lockdown measures affected stock returns, an event study methodology is employed to detect the presence of abnormal returns around each event date. Using a set of 21 events and a 5-day event window for each event, the abnormal returns are analysed with parametric and nonparametric tests. The test results show a negative market response over strict lockdown announcements, and a positive response over the withdrawals of such restrictions. The results suggest investors are likely to respond negatively to government’s impositions, especially in extraordinary situations. Nevertheless, the impact declines as the period of impositions extends. In addition, the companies most affected by the Portuguese government impositions are Ibersol and EDP Renováveis, while the least affected companies are Jerónimo Martins and Pharol.